Genetic parameters for rank of the Santa inês sheep in agricultural fairs using bayesian procedures - Alves, Anderson Antonio Carvalho [UNESP]; Lôbo, Ana Maria Bezerra Oliveira; Facó, Olivardo; da Silva, Luciano Pinheiro; Lôbo, Raimundo Nonato Braga (Taylor & Francis, 2016)
The aim of this study was to estimate the genetic parameters for the ability of a sheep to rank among the top three in its age category (ABI3) and for its total score (TS) on the judgement championships held in different agricultural fairs in Brazil. Data files included 3180 records referring to 1896 animals for ABI3 and 4383 records referring to 2170 animals for TS. The relationship matrix was composed by 4069 animals. Variance components were estimated fitting threshold and linear animal models for ABI3 and TS,respectively,by Bayesian analysis using the Gibbs sampler. The posterior means of the heritability and repeatability were,respectively,0.10 ± 0.07 and 0.57 ± 0.11 for ABI3 and 0.12 ± 0.04 and 0.31 ± 0.02 for TS. The low values for the heritabilities related to these traits reveal a strong influence of the environmental factors,as the differential management offered to the animals before and during the fair. The repeatability values for ABI3 suggest high correlation among the animal classifications in different fairs. However,for TS,the observed performance has moderate confidence to be repeated over time. We conclude that although reduced,there is genetic variability for the animal’s performance in agricultural fairs. Nevertheless,due to the low heritability estimates,the expected response to direct selection for ABI3 and TS will be low.
Keywords: Animal judging; Bayesian methods; Heritability; Repeatability; Threshold traits